Additive manufacturing of high-strength continuous fiber reinforced polymer composites - Parandoush, Pedram (Kansas State University, 2019)
Additive manufacturing (AM), also referred to as 3D printing, of polymer-fiber composites has transformed AM into a robust manufacturing paradigm and enabled producing highly customized parts with significantly improved mechanical properties compared to un-reinforced polymers. 3D printing of continuous carbon fiber reinforced thermoplastics (CFRTP) composites is increasingly under development owing to its unparalleled flexibility of manufacturing 3D structures over traditional manufacturing processes. However, key issues, such as weak interlayer bonding, voids between beads and layers, and low volume ratio of carbon fiber, in the mainstream fused deposition modeling (FDM) and extrusion suppress the applications of these techniques in mission-critical applications, such as aerospace and defense industries. In this work, we proposed a new laser assisted AM method that utilizes prepreg composites with continuous fiber reinforcement as feedstock to fabricate 3D objects by implementing laser assisted bonding and laser cutting. This technique is inspired by laminated object manufacturing (LOM), for AM of continuous CFRTPs using prepreg composite sheets. AM of continuous glass and carbon fiber reinforced thermoplastic composites is demonstrated using this technique. The continuous fiber reinforced prepreg is laser cut and laser bonded layer upon layer to produce 3D composite objects. Microstructure and mechanical properties (strength, modulus, interfacial, and shear properties) of the additively manufactured continuous fiber composites are studied and compared to other additive and conventional manufacturing methods. The interlayer properties of these additively manufactured composites was superior to other AM technologies, resulting to an excellent mechanical properties relative to other AM techniques. The microstructure analysis, by micro computed tomography (CT) scans, scanning electron microscopy (SEM), and optical microscopy, showed low void content and full consolidation of prepreg layers. The temperature at the material interface during the 3D process is crucial to achieve a strong bonding strength. This temperature can be predicted via the developed finite element (FE) heat transfer model in this work. This numerical model is able to predict the temperature history during the laser bonding process with great accuracy when compared to the experimental values. The surface quality of the additively manufactured CFRTPs were also studied and compared with the FDM technology. In addition, mechanical finishing methods, namely CNC milling and rotary ultrasonic machining (RUM), were employed to improve the surface quality of the 3D printed composites and drill precise holes in the structures. Overall, the proposed AM method can be broadly beneficial for industries requiring high performance and lightweight structural materials with complex geometries. This method is also easily scalable for high volume productions and could additionally reduce the waste associated with current CFRTP production techniques and improve the process from the production time standpoint by automation.
Keywords: Carbon fiber; Composite; Additive manufacturing; 3D printing